(untitled) (Bangladesh Journal of Medical Science, 2018)
Background and objective: Through contaminated hands, number of infectious disease can be transmitted from one person to another. Salmonella spp, E. coli O157, norovirus and adenovirus that can cause diarrheal and respiratory infections are transmitted either directly or indirectly via contaminated objects. Children are at higher risk of getting such infections as they lack natural immunity and understanding of the importance of good hygiene. Hand washing is one of the most important factors in controlling the spread of the microorganisms. This study aimed to determine the knowledge and attitude of hand washing and the hand washing technique, in relation to “Bacterfree Hand Intervention” among pre-schoolers. Materials and methods: This cluster-randomized trial involved 146 pre-schoolers from 3 different pre-schools in Wilayah Persekutuan was conducted from April to August 2015.Participants were interviewed twice; pre and post intervention. Face-to-face interview was done using guided questionnaires that include questions on knowledge and attitude of hand washing and its techniques. A group of students were given single intervention i.e. posters and the other group participated in “Bacterfree Hand Intervention” program which consisted of storytelling, posters and demonstration. Results: There were significant increase of knowledge (median (10.00 vs 11.00, P< 0.001) and technique(6.00 vs 6.00, P = 0.020) after intervention in single intervention group while the attitude (median 6.00 vs 6.00, P= 0.871) was remained unchanged. Meanwhile, the median of knowledge, attitude and hand washing techniques in multiple intervention group increased significantly after intervention. Conclusions: This study highlighted the need of comprehensive educational programs that include various mode of delivery to create awareness regarding the importance of hand hygiene among pre-school children. This is very important to establish healthy environment and eventually prevent communicable diseases in the community. Bangladesh Journal of Medical Science Vol.17(1) 2018 p.67-70